2016
DOI: 10.1021/acs.molpharmaceut.6b00227
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast Enhanced MRI Assessing the Antiangiogenic Effect of Silencing HIF-1α with Targeted Multifunctional ECO/siRNA Nanoparticles

Abstract: Stabilization of hypoxia inducible factor 1α (HIF-1α), a biomarker of hypoxia, in hypoxic tumors mediates a variety of downstream genes promoting tumor angiogenesis and cancer cell survival as well as invasion, and compromising therapeutic outcome. In this study, dynamic contrast enhanced MRI (DCE-MRI) with a biodegradable macromolecular MRI contrast agent was used to noninvasively assess the antiangiogenic effect of RGD-targeted multifunctional lipid ECO/siHIF-1α nanoparticles in a mouse HT29 colon cancer mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…28 Some integrins, including αvβ3 and αvβ5, are overexpressed in neovasculature and some tumors including ovarian cancer (OvCa). 2931 Since the RGD motif is recognized by half integrins, RGD-containing peptides have been widely used as targeting ligand for cancer diagnosis 3235 and therapy 3640 .…”
Section: Introductionmentioning
confidence: 99%
“…28 Some integrins, including αvβ3 and αvβ5, are overexpressed in neovasculature and some tumors including ovarian cancer (OvCa). 2931 Since the RGD motif is recognized by half integrins, RGD-containing peptides have been widely used as targeting ligand for cancer diagnosis 3235 and therapy 3640 .…”
Section: Introductionmentioning
confidence: 99%
“…A multifunctional, pH-sensitive, cationic lipid carrier (1aminoethyl) imino bis[N-(oleicylcysteinyl-1-amino-ethyl) propionamide] (ECO) was synthesized for the systemic and targeted delivery of HIF-1α siRNA. [79] Tumor-targeted ECO/siRNA nanoparticles were formed by conjugating cRGD-PEG to the complex of ECO and HIF-1α siRNA. The pH-sensitive amphiphilicity of ECO facilitated endosomal escape and avoided degradation of the siRNA cargo within the acidic environment.…”
Section: Hypoxia Targeted/responsive Sirna Deliverymentioning
confidence: 99%
“…Systemic administration of ECO/siHIF-1α nanoparticles at a dose of 2.0 mg of siRNA kg −1 every 3 days for 3 weeks resulted in >50% reduction in tumor size compared to a saline control. [79] Liu et al reported a cationic mixed micellar nanoparticle (MNP) consisting of two amphiphilic di-block copolymers, poly(ε-caprolactone)-block-poly(2aminoethylethylene phosphate) (PCL 29 -b-PPEEA 21 ) and poly(εcaprolactone)-block-poly(ethylene glycol) (PCL 40 -b-PEG 45 ) for the treatment of hypoxic tumors. [80] MNP formed a nanocomplex of 58.0 ± 3.4 nm after binding with HIF-1α siRNA.…”
Section: Hypoxia Targeted/responsive Sirna Deliverymentioning
confidence: 99%
“…Preclinical studies in various different tumor models have demonstrated siRNA nanoparticles to be effective in inhibiting tumor growth (Parvani et al 2015; Su, et al 2015; Zhang, et al 2016), metastasis (Parvani et al 2015; Zhao, et al 2015), angiogenesis (Liu, et al 2015; Malamas, et al 2016), and drug resistance (Deng et al 2013; Zhang et al 2016). These studies have paved the way for various ongoing clinical trials, which are summarized in Table 2.…”
Section: Clinical Application Of Sirna Nanoparticles In Cancer Treatmentmentioning
confidence: 99%